Which is a better marker for overweight: waist height ratio or waist circumference? - Anwar, Sanam; Aleem, Bushra; Rashid, Hajir H.; Moslhey, Ghadeer J. (International Journal of Research in Medical Sciences, 2019)
Background: The global prevalence of obesity has been increasing. Body mass index, waist circumference and waist height ratio have been widely used for nutritional assessment. Waist height ratio has the advantage of taking into account abdominal obesity as well as height associated with body fat accumulation or distribution. The objective of this study was to suggest cut off points for waist circumference and waist height ratio to identify overweight in Omani adults. Methods: Weight, height, waist circumference and waist height ratio were measured for all participants. Pearson’s correlation was used to determine correlation of BMI with waist circumference and waist height ratio. ROC curve was used to identify AUC and specific cut off point for anthropometric indicators. Results: The largest proportion of overweight was picked up by waist height ratio across both the genders. Correlation of BMI with waist height ratio was stronger (r=0.699) than correlation with waist circumference (r=0.589) for both the genders. Maximum AUC was for waist height ratio in males (AUC=0.833, 95% CI=0.791-0.875). The specific cut off point for waist circumference in males and females was 89.5cm and 87.6cm respectively. The specific cut off point for waist height ratio in males and females was 0.53 and 0.57 respectively. Conclusions: Maximum participants were found overweight by waist height ratio followed by waist circumference and the least by BMI. The higher cut off points should be used in this population for identifying overweight people.